PERILAKU PETANI KELAPA SAWIT POLA SWADAYA DAN POLA PLASMA TERHADAP PRAKTIK PRODUKSI KELAPA SAWIT BERKELANJUTAN DI KABUPATEN KAMPAR, RIAU - Fitri Yutika; Eko Ruddy Cahyadi; Heti Mulyati (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2019)
Indonesian palm oil plantation industry is confronted with sustainability issues that potentially restrict trade access in theglobal market. Smallholders are actors who have an important role in palm oil plantation sustainable development. Theory of Planned Behavior (TPB) and past behavior are used as the theoretical basis to see the influence of attitude toward sustainability, subjective norm, perceived behavioral control and past behavior toward smallholders' intention to implement sustainable palm oil production practices. This study aims to analyze differences in smallholders' intention to implement sustainable palm oil production practices between independent farmers and plasma farmers. The study sample consisted of 121 independent farmers and 121 plasma farmers wich is spread across Kampar Regency. Data collection was done by distributing questionnaires and analyzed using Structural Equation Modeling (SEM) with Partial Least Square (PLS) program. The result of this study indicates that attitude toward sustainability, subjective norm, perceived behavioral control and past behavior have a positive and significant effect on plasma farmers' intention to implement sustainable palm oil production practices, whereas subjective norm has no effect on the independent farmers' intention to implement sustainable palm oil production practices.